A Study of Nonlinear Fractional-Order Boundary Value Problem with Nonlocal Erdelyi-Kober and Generalized Riemann-Liouville Type Integral Boundary Conditions - Ahmad, Bashir; Ntouyas, Sotiris K.; Tariboon, Jessada; Alsaedi, Ahmed (Mathematical Modelling and Analysis, 2017)
We investigate a new kind of nonlocal boundary value problems of nonlinear Caputo fractional differential equations supplemented with integral boundary conditions involving Erdelyi-Kober and generalized Riemann-Liouville fractional integrals. Existence and uniqueness results for the given problem are obtained by means of standard fixed point theorems. Examples illustrating the main results are also discussed.